THE OLD ROOTS OF THE NEW AESTHETICS : Review of CORNEL-FLORIN MORARU, The scientific turn of contemporary aesthetics. Avant-garde research in the fields of neuroscience and artificial intelligence, Eikon Publishing House, Bucharest, 2022, 345 p. (Analele Universității București.Filosofie, 2024)
Individuals with an inclination towards the great tradition of European culture do not want to take note of the scientific-technological evolution of the last decades, and scientists do not want to know of the existence of a cultural tradition that preceded them. The contemporary intellectual landscape seems to be marked by a massive split between two apparently irreconcilable attitudes. For all their differences, both sides believe that the contemporary evolution of technology has overturned the fundamental concepts that have permeated European culture from Homer to Heidegger.